Exploring the hidden treasure in arid regions: pseudocereals as sustainable, climate-resilient crops for food security - Manoharan, Ramya; Asthana, Sugandha; Somanathan Nair, Chythra; Gokhale, Trupti; Nishanth, Drishya; Jaleel, Abdul; Sood, Neeru (Frontiers in Plant Science, 2025)
Agricultural productivity needs to grow in a sustainable way to eradicate hunger and malnutrition, as outlined in the 2030 Agenda for Sustainable Development (SDGs). The demand for healthy, nutritious food is expected to rise by 50% between 2012 and 2050 as the world’s population grows. Even today, more than 800 million people face chronic hunger, while 2 billion suffer from micronutrient deficiencies. These challenges are further intensified by climate change stressors. Around 90% of the world’s farmland is affected by climate-related stress, which in some areas can cut crop production by as much as 70%. Countries near the equator, particularly arid lands, are evenly affected, where food security and sustainability are increasingly threatened by rising global food demand and worsening climatic conditions. Relying only on traditional staple crops like rice, wheat, and maize is not enough, and there is a need to explore alternative crops which are climate resilient and could contribute to food security. This review focuses on pseudocereals—crops such as amaranth, quinoa, and buckwheat. These are not true cereals but are rich in nutrients and can survive in difficult environments such as during drought, in salty soils, and at extreme temperatures. Pseudocereals such as amaranth, quinoa, and buckwheat are non-grass crops with dense nutrients. The review covers how pseudocereals can help with food security, improve health, and be used in industry. Some studies have shown that the bioavailability of pseudocereals can be increased by various processing techniques. However, these crops are mostly grown in their native regions because seeds are hard to get and markets are limited. Pseudocereal production must be expanded globally supported by strategies such as conservation of its wild species, molecular advance techniques, policies, farming practices, and integration of indigenous knowledge. Particularly, in arid regions where traditional crops face many challenges due to harsh climatic conditions and limited water resources, integrating these pseudocereal crops into their agronomy system and commodity markets could serve as a roadmap in achieving sustainable development goals (SDGs). These crops could also help other vulnerable regions around the world that face hunger and poor nutrition.